'Radial force' of colonic stents: A parameter without consistency, definition or standard - Hans-Ulrich Laasch; Graham D. Milward; Derek W. Edwards (Society of Gastrointestinal Intervention, 2020)
Background: To investigate the expansion force of current colonic stents and to match these to industry standards. Methods: Samples of all colonic stents were requested from manufactures world-wide. Expansion forces were tested with an RX650 compression tool (MSI, Flagstaff, AZ, USA). Measurements were averaged over three cycles of compression and expansion, independently performed at 37°C by specialist engineers of MSI. In parallel, a survey was undertaken on standards, and tests used by manufacturers in their production process. As a labbased study, Institutional Review Board approval was not required. Results: A literature search did not identify any industry standards for testing expansion force or a suggested range for this primary stent function. Median expansion force of all stents was 24.4 N, (35.1 N for braided, 20.7 N for knitted stents) with a vast range from 5.6-130.8 N. Covering braided stents in liquid silicone increased their median force 5.5-fold, separate membranes attached to knitted stents only had a minor effect on expansion force. Five of eight manufacturers replied, describing three different test methods with three different units for expansion force. Conclusion: There are no standards on assessing expansion force, or what the ideal range should be. Consequently, the variation is remarkable, but values are not published, and even if they were, they could not be compared. Consequently, interventionists are unable to discriminate between different stents and to select the most suitable device for their patients, and no recommendation can be made on the 'best stent'. The industry needs an agreed test standard and an acceptable range of stent forces.